León educators on the brink of the Spanish civil war. Boom, purification and paralysis - Raquel POY CASTRO (Ediciones Universidad de Salamanca, 2012)
In this article we examine educators and educational institutions in the Spanish city of León at the beginning of 1930. We begin by providing a historical overview that delineates Leonese educators' general social conditions and social impact in precivilian war of 1936-1939 society. We then analyse the role of educational movements and, more specifically, the progressive intellectual groups affiliated with republican and liberal institutions versus vs the conservative ones with the Catholic Church, in the political conflict that occurred during the Spanish Second Republic (1931-1939). The article stresses the growing public activity of such educational groups and the participation of teachers and professors in the development of modern education in the early XX th century in Spain. The article also deals with the increasing distance between these educational groups due to the prevalence of political conflict in the period.